Strategy in the contemporary world an introduction to strategic studies - Baylis, John 1946-; Wirtz, James J.; Gray, Colin S. (Oxford University Press, 2013)
Strategy in the Contemporary World brings together world leading experts to provide a comprehensive introduction to the role of military power in today's world. The definitive textbook on the subject, the fifth edition explores both the enduring and historical issues which have shaped the study of strategy and the contemporary issues that dominate today's headlines.The new edition has been substantially updated to reflect the changing structure of global politics and rapid technological developments, with the inclusion of four brand new chapters: History of the Practice of Strategy, Geopolitics and Grand Strategy, Strategy and Defence Planning, and Theory and Practice of Continental Warfare.